Mathematical Connection Ability Based on Self-Efficacy in IDEAL Problem Solving Model Assisted by ICT - Ningrum, Herlina Ulfa; Mulyono, Mulyono; Isnarto, Isnarto (Unnes Journal of Mathematics Education Research, 2020)
Mathematical connection ability and self-efficacy are important for students possess in learning mathematics. A learning model is needed that can help students improve their mathematical connection ability and self-efficacy, namely IDEAL Problem Solving assisted by ICT. The research aims (1) to determine the quality of IDEAL Problem Solving assisted by ICT on students’ mathematical connection ability and (2) to determine students' mathematical connection ability based on self-efficacy. The study used a mixed method with a quantitative first stage and continued qualitatively. The student population is students of class X SMA N 6 Semarang with two sample classes. The results showed that (1) IDEAL Problem Solving learning assisted by ICT is quality for students' mathematical connection ability; (2) students with high self-efficacy have mathematical connection ability in all four indicators, students with medium self-efficacy, almost have all indicators of mathematical connection ability but on indicators connecting mathematical concepts with daily life, students have not fulfilled these indicators well, while students with low self-efficacy do not yet have complete mathematical connection ability for all indicators.